Going beyond templates - Seco, João Costa (2024)
Publisher Copyright: © The Author(s) 2024. Acknowledgements Partially supported by Grant Lisboa-01-0247-Feder-045917. Funding Open access funding provided by FCT|FCCN (b-on).